2007
DOI: 10.3113/fai.2007.0214
|View full text |Cite
|
Sign up to set email alerts
|

Foot and Ankle Injuries in Elite Female Gymnasts

Abstract: Elite female gymnasts can sustain significant injury to the foot and ankle region. In our study, Lisfranc injuries were most likely career-ending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 4 publications
1
35
1
Order By: Relevance
“…2,3 This study revealed that the injury also limits young patient's activity in most cases (three of the five cases), which supports the results from other adult studies describing the injured foot becoming painful during exercise and limiting sport and leisure activities. 2,4,6,12,15,16 Other complications associated with Lisfranc injuries are loss of foot position, forefoot ischemia, skin necrosis, and late degenerative changes. 4,[6][7][8]17 In this research, degenerative changes were found only in one patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 This study revealed that the injury also limits young patient's activity in most cases (three of the five cases), which supports the results from other adult studies describing the injured foot becoming painful during exercise and limiting sport and leisure activities. 2,4,6,12,15,16 Other complications associated with Lisfranc injuries are loss of foot position, forefoot ischemia, skin necrosis, and late degenerative changes. 4,[6][7][8]17 In this research, degenerative changes were found only in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…As this research also revealed, common causes for Lisfranc injuries are car and motorcycle accidents and falls or jumps from a height, but it should be noted that also a minor trauma such as simple foot sprain in sports or a fall from stairs can cause a significant tarsometatarsal injury. [3][4][5]8,9,[11][12][13] Pain, edema, and hematoma are common symptoms after the injury and abduction-pronation movement usually induces pain in the injured foot. 3,14 In this research, the anatomical reduction was well achieved in all but one case, which supports the recommendation that Lisfranc injuries in adolescents should be treated operatively.…”
Section: Discussionmentioning
confidence: 99%
“…23 Furthermore, gymnastics also produces the highest number of injuries requiring surgeries. 24 Girls aged 12 to 17 have a greater number of injuries sustained (7.4 per 1000 participants) than girls aged 6 to 11 (3.6 per 1000 participants). 22 The potential areas for injury include the wrist and hand, the spine, and the ankle and foot.…”
Section: Soccermentioning
confidence: 94%
“…1,19 Very young athletes who continue to participate in jumping sports may require repeat spur removal.…”
Section: Resultsmentioning
confidence: 99%
“…1,19 In addition to gymnastics, the syndrome is seen in basketball, soccer, football, and track distance running. It can also be seen after nonsporting injuries—especially, fractures—about the ankle and foot.…”
Section: Pathoanatomy Of Medial Impingementmentioning
confidence: 99%